PENGARUH ETOS KERJA TERHADAP KOMITMEN KERJA GURU DI SMK DARUNNAJAH 2 CIPINING - Marine Khoirunnisa Kasit; Nailil Muna Shalihah; Musthofa Zahir (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Job stress can affect an individual's performance and well-being at work. The pressure faced by employees, whether originating from excessive workloads, tight time demands, or unclear roles, can cause anxiety, fatigue, and decreased productivity. Prolonged work stress can lead to mental and physical health problems, such as sleep disorders, depression, and even heart problems. Therefore, it is important for companies to create a work environment that supports work-life balance and provides support to reduce stress, to ensure employees remain healthy, motivated and productive. This research approach uses quantitative survey methods. The research sample in this study used a population of all teachers at SMK Darunnajah 2 Cipining 33 Teachers. The research data collection technique was carried out using questionnaires and documentation. The research procedure begins with preparing the grid, preparing the instrument, carrying out a trial, the trial results are tested for validity and reliability, improving the instrument, then the instrument is used to retrieve data. The calculation results show the regression equation Ý = 26,888 + 0.517 Because the sig value. Fchange < 0.05, then the decision is H1: accepted and H0 rejected. This means it is significant. So it can be concluded that work ethic has a positive and significant effect on Teacher Work Commitment. The simple correlation coefficient value of rxy = 0.940 and the variance significance test is 85.4%, while the remaining 15.5% of teacher work commitment is influenced by other variables.